Crop protection with plant extracts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Farmers often use plant extracts to protect their crops against parasites but the information on the plants and methods used is scattered and very sketchy. 'The Information Network for Crop Protection with Plant Extracts' is aiming to collect and...